Use of Functional Starters of Spontaneous Fermentation for Bakery Production (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The aim of the study is to improve the quality of wheat bread and to ensure its microbiological stability by improving the technology for the production of leaven of spontaneous fermentation.